2013
DOI: 10.1093/europace/eus401
|View full text |Cite
|
Sign up to set email alerts
|

An 8-year single-centre experience of cardiac resynchronisation therapy: procedural success, early and late complications, and left ventricular lead performance

Abstract: Transvenous implantation of the LV lead is safe and achievable for CRT with high procedural success rates. For the first time we describe the late complications from CRT in different heart failure populations. This group of patients must be kept under surveillance, not only for heart failure events but also for device-related issues. The reasons for higher complication rates in DCM patients require further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Procedural data in the NC group are comparable with those reported in the literature. For example, a recent study reported a 167±109 min total procedural time, with a mean fluoroscopy time of 30±9.3 min in non-complicated implantations performed in a highly experienced center [9]. Our results are in line with the recent study of Kowalczyk J et al who reported a 15.4 % contrast-induced acute kidney injury after CRT implantation in patients with GFR≤60 mL/min/1.73 m 2 [6].…”
Section: Discussionsupporting
confidence: 90%
“…Procedural data in the NC group are comparable with those reported in the literature. For example, a recent study reported a 167±109 min total procedural time, with a mean fluoroscopy time of 30±9.3 min in non-complicated implantations performed in a highly experienced center [9]. Our results are in line with the recent study of Kowalczyk J et al who reported a 15.4 % contrast-induced acute kidney injury after CRT implantation in patients with GFR≤60 mL/min/1.73 m 2 [6].…”
Section: Discussionsupporting
confidence: 90%
“…While no peri‐procedural thromboembolic events occurred, the incidence of peri‐procedural major bleeding caused by a pocket haematoma needing revision was 4.3%; in the follow‐up, at a median of 1 month from TLE procedure, the cumulative incidence of pocket haematoma was even higher and reached 6%, thus exposing patients to a high risk of device‐related infection . These rates are higher compared to those observed from large patient cohort studies treated with de novo CRT device implant procedure, which ranged between 0 and 3.3%, and outline the importance of adequate peri‐procedural anticoagulation management. Oral anticoagulation therapy was found to be an independent predictor of both any AE and SAE after TLE.…”
Section: Discussionmentioning
confidence: 99%
“… 26 In a recent study from a single centre in the UK (2000–2009), CRT-D exceeded 80% of implants for CRT. 27 …”
Section: Discussionmentioning
confidence: 99%